Can economic incentives increase the use of home dialysis?. Issue 5 (13th July 2018) - Manns, Braden; Agar, John W M; Biyani, Mohan; Blake, Peter G; Cass, Alan; Culleton, Bruce; Kleophas, Werner; Komenda, Paul; Lobbedez, Thierry; MacRae, Jennifer; Marshall, Mark R; Scott-Douglas, Nairne; et al.
Abstract: There are advantages to home dialysis for patients, and kidney care programs, but use remains low in most countries. Health-care policy-makers have many levers to increase use of home dialysis, one of them being economic incentives. These include how health-care funding is provided to kidney care programs and dialysis facilities; how physicians are remunerated for care of home dialysis patients; and financial incentives—or removal of disincentives—for home dialysis patients. This report is based on a comprehensive literature review summarizing the impact of economic incentives for home dialysis and a workshop that brought together an international group of policy-makers, health economists and home dialysis experts to discuss how economic incentives (or removal of economic disincentives) might be used to increase the use of home dialysis. The results of the literature review and the consensus of workshop participants were that financial incentives to dialysis facilities for home dialysis (for instance, through activity-based funding), particularly in for-profit systems, could lead to a small increase in use of home dialysis. The evidence was less clear on the impact of economic incentives for nephrologists, and participants felt this was less important than a nephrologist workforce in support of home dialysis. Workshop participants felt that patient-borne costs experienced by home dialysis patients were unjust and inequitable, though participants noted that there was no evidence that decreasing patient-borne costs would increase use of home dialysis, even among low-income patients. The use of financial incentives for home dialysis—whether directed at dialysis facilities, nephrologists or patients—is only one part of a high-performing system that seeks to increase use of home dialysis.